2016
DOI: 10.1007/s11239-015-1314-3
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacology of anticoagulants used in the treatment of venous thromboembolism

Abstract: Anticoagulant drugs are the foundation of therapy for patients with VTE. While effective therapeutic agents, anticoagulants can also result in hemorrhage and other side effects. Thus, anticoagulant therapy selection should be guided by the risks, benefits and pharmacologic characteristics of each agent for each patient. Safe use of anticoagulants requires not only an in-depth knowledge of their pharmacologic properties but also a comprehensive approach to patient management and education. This paper will summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(135 citation statements)
references
References 74 publications
0
110
0
17
Order By: Relevance
“…Therefore, the aPTT may underestimate high concentrations, posing a significant problem in overdose assessment . When a more sensitive assay (e.g., ECT, dTT) is unavailable, the aPTT may provide qualitative assessment of dabigatran . Because sensitivity of different assays vary, checking the sensitivity of aPTT to dabigatran at each institution is recommended .…”
Section: Laboratory Coagulation Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the aPTT may underestimate high concentrations, posing a significant problem in overdose assessment . When a more sensitive assay (e.g., ECT, dTT) is unavailable, the aPTT may provide qualitative assessment of dabigatran . Because sensitivity of different assays vary, checking the sensitivity of aPTT to dabigatran at each institution is recommended .…”
Section: Laboratory Coagulation Monitoringmentioning
confidence: 99%
“…Because sensitivity of different assays vary, checking the sensitivity of aPTT to dabigatran at each institution is recommended . A normal aPTT does not exclude clinically relevant dabigatran activity …”
Section: Laboratory Coagulation Monitoringmentioning
confidence: 99%
“…We note that Rudd et al have reported independently on possible rivaroxaban failure in patients treated during the postpartum period, possibly due to pharmacokinetic alterations seen in the postpartum period that can contribute to decreased drug exposure and reduced anticoagulant efficacy [16]. In fact, rivaroxaban is well known to be metabolized by the cytochrome P450 isoenzyme CYP 3A4 and binds to P-glycoprotein; hence, leading to risks of pharmacokinetic interactions that may alter its anticoagulant properties [17]. In practice, it may be best at this time to choose between these several available anticoagulant drugs on a case-by-case basis, taking into account patient preferences, monitoring constraints, difficulty controlling the INR, the risk of bleeding and interactions, and the cost of treatment [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in healthy volunteers suggest that obesity has only modest effects on the pharmacokinetic profile of dabigatran, rivaroxaban, or apixaban and that dose adjustments for obesity may not be necessary. 29 For thromboprophylaxis after orthopedic surgery, a meta-analysis found similar efficacy and safety of DOACs in elderly obese and non-obese patients. 30 A meta-analysis of the major DOAC trials for treatment of VTE found no difference in efficacy or major bleeding between subgroups of patients with body weight ,100 kg vs .100 kg.…”
Section: Doacsmentioning
confidence: 99%